Ambulatory blood pressure monitoring for hypertension in general practice. - Taylor, R S (1998)
Ambulatory blood pressure monitoring (ABPM) is being increasingly used in general practice. There is at present little published evidence regarding the clinical utility of ABPM in the care of patients with established hypertension in this setting. We examined this issue by undertaking ABPM in a group of patients with established hypertension. 40 patients (aged 33-60 years) currently being treated for hypertension were randomly selected from a general practice list and underwent a single 24-hour ABPM study. ABPM values were compared with clinic blood pressure (CBP) values obtained on the day of monitoring together with previous readings taken by the general practitioner (GP). In the case of mean arterial pressure, 24-hour, awake and asleep ABPM values were found to underestimate CBP values by 14 mmHg (95% confidence interval 11-16 mmHg), 9 mmHg (95% C16-12 mmHg) and 24 mmHg (95% CI 21-27 mmHg), respectively. When used to classify blood pressure control, ABPM values produced equivalent results to CBP except by the criterion of BP load, for which 24-hour ABPM showed a higher rate of unsatisfactory control. 5 patients classified by CBP to have satisfactory BP control according to current international guidelines were found to have unsatisfactory BP control by ABPM. This study demonstrates the potential value of ABPM in patients with essential hypertension in a general practice setting. ABPM provided information over and above that obtained by CBP in a substantial proportion of patients.